Stacked trees: a new hybrid visualization method - Bisson, Gilles; Blanch, Renaud (AVI'12: Proceedings of the Working Conference on Advanced Visual Interfaces, 2012)
In this paper, we introduce a new Focus+Context visualization technique, named ``Stacked Trees'', allowing us to explore large dendrograms produced by hierarchical clustering. This approach displays up to fifty thousands nodes on a standard-sized screen.